1190 Engaging Patients And Family Members To Understand What Matters Most Living With Obstructive Sleep Apnea. (27th May 2020) - Mou, J; Silva, A; Figetakis, K; Ho, S S; Williams, M; Mebust, K A; Xia, Y; Xie, J; Wang, J; Chin, N; Vondran, R; Vondran, R
Abstract: Introduction: As a common but modifiable chronic condition, obstructive sleep apnea (OSA) has been identified as the top secondary cause of many other diseases including cardiovascular diseases and type 2 diabetes. Diagnosing and managing OSA provides neurological, cardiovascular and metabolic benefits, however real-world studies indicate disconnections between evidence and outcomes. Using an engagement approach and qualitative design, this project aims to better understand care and research gaps in OSA in a community healthcare setting. Methods: Methods: Patient and family representatives were identified and recruited through OSA support meetings hosted by MultiCare Sleep Medicine Centers, to form a board of 12, with three key patient advocates. Six meetings, each facilitated by one or two members of the board, were held to encourage focus group discussion and accommodate interactive conversations on the topic. Discussions were audio recorded and edited to exclude patients' identifiable information, then transcribed. Manual open coding was completed by two coders for each transcription to develop a codebook, followed by auto-coding and inductive content analysis using Nvivo 11. Results: All enrolled patients had diagnosed moderate-to-severe OSA and were prescribed with continuous positive airway pressure (CPAP) therapy. Two participants were African American and one was multiethnic. Patients' age ranged from early 30s to 80s. Seven main themes were identified: OSA diagnostic issues; treatment experiences and options; comorbidities; patient community and support needs; long-term management challenges beyond "compliance"; knowledge of OSA, CPAP and care; and patient-driven research. The first few weeks after CPAP initiation appeared to be a critical time window that impacted patients' adaptation and use. Conclusion: Our study revealed barriers and facilitators in OSA diagnosis and treatment. Results showed highly prevalent chronic co-morbidities and the needs to care for patients in the comorbid scenario. It was highlighted that a paradigm of patient-centered care and research is lacking and warranted. Participants also called for better coordination between sleep medicine, primary care, other specialists, durable device suppliers and insurance. Key research efforts are expected to focus on the first 30-day post CPAP dispense to improve compliance. Support: Patient Centered Outcomes Research Institute (PCORI) (Contract #: 7717241)